2000
DOI: 10.1021/bi992205u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aromatic Residues at the Ends of Transmembrane α-Helices on Helix Interactions with Lipid Bilayers

Abstract: We have studied the effects of aromatic residues at the ends of peptides of the type Ac-KKGL(n)()WL(m)()KKA-amide on their interactions with lipid bilayers as a function of lipid fatty acyl chain length, physical phase, and charge. Peptide Ac-KKGFL(6)WL(8)FKKA-amide (F(2)L(14)) incorporated into bilayers of phosphatidylcholines containing monounsaturated fatty acyl chains of lengths C14-C24 at a peptide:lipid molar ratio of 1:100 in contrast to Ac-KKGL(7)WL(9)KKA-amide (L(16)) which did not incorporate at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 37 publications
3
66
0
Order By: Relevance
“…In addition to stabilizing the concentration of monomer in aqueous solutions, inclusion of any C-terminal aromatic residue provided a lipid/water interfacial anchor. As was seen with W, F residues are commonly present (and Y to a lesser extent) at the hydrophobic/hydrophilic interface for TM segments of membrane proteins (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007 Comparing all of the summarized data in Tables 3 and 4 and the profiles shown in Figs. 16 and 17, the sequences displaying the highest ion transport activity and the second and third most left-shifted k 1/2 values are both W containing peptide sequences, NK 4 -M2GlyR-p22 T19R, S22W and NK 4 -M2GlyR-p22 Q21W, S22R.…”
Section: Wt S22wmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition to stabilizing the concentration of monomer in aqueous solutions, inclusion of any C-terminal aromatic residue provided a lipid/water interfacial anchor. As was seen with W, F residues are commonly present (and Y to a lesser extent) at the hydrophobic/hydrophilic interface for TM segments of membrane proteins (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007 Comparing all of the summarized data in Tables 3 and 4 and the profiles shown in Figs. 16 and 17, the sequences displaying the highest ion transport activity and the second and third most left-shifted k 1/2 values are both W containing peptide sequences, NK 4 -M2GlyR-p22 T19R, S22W and NK 4 -M2GlyR-p22 Q21W, S22R.…”
Section: Wt S22wmentioning
confidence: 55%
“…A propensity for tryptophans residing at the aqueous/lipid interface also had been observed and tested by others (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007). Placing a W at the Cterminus sets the registry of the TM segment that spans the bilayer.…”
Section: M2glyr Studiesmentioning
confidence: 90%
“…Following the positive inside rule, they are preferentially located on the cis-side of membranes, (12), where they associate with anionic phospholipids (13), fulfilling a topology-determining role (14). When flanking a hydrophobic R-helix in transmembrane model peptides, lysines showed a distinct preference for the hydrophilic side of the interfacial region, close to the phosphate groups of the surrounding lipid bilayer (5).To gain more insight in these interfacial interactions, model peptides have been used (5,15,16). An example of synthetic model peptides are the so-called WALP 1 peptides (17).…”
mentioning
confidence: 99%
“…To gain more insight in these interfacial interactions, model peptides have been used (5,15,16). An example of synthetic model peptides are the so-called WALP 1 peptides (17).…”
mentioning
confidence: 99%
“…(8) and also within the membrane-spanning regions of the Cx26 atomic model (10). Tryptophan substitutions were avoided at predicted membrane boundaries as large aromatic side chains can influence positioning of helices within the membrane (32). In the Cx26 crystal structure, helices TM2 and TM3 extend beyond the membrane at the cytosolic face (10), and these cytoplasmic regions were not analyzed in this study.…”
Section: Methodsmentioning
confidence: 99%